Life-threatening onset of coeliac disease: a case report and literature review - Roberto De Giorgio; Umberto Volta; Giacomo Caio; Lisa Lungaro; Giorgio Zoli; Matteo Guarino; Edoardo Gambuti; Franco Alfano; Andrea Strada; Rachele Ciccocioppo (BMJ Open Gastroenterology, 2020)
Background Coeliac disease (CD) results from an immune-mediated reaction to gluten in genetically predisposed individuals. In rare cases CD may occur with acute features deferring the diagnosis and exposing these patients to possible life-threatening complications. Herein we present the case of a young woman with a coeliac crisis, that is, a sudden clinical onset characterised by severe electrolyte imbalance due to an unknown (previously unrecognised) CD.Methods This is a case report and literature review revealing that coeliac crisis is under-reported, with a total of 48 adult cases so far published. The diagnosis in our case was established by histopathological analysis of multiple duodenal biopsies. The patient’s serum was tested by enzyme-linked immunoassay to detect antitransglutaminase IgA antibodies.Results In contrast to cases reported in the literature, with male gender predominance and a mean age of 50±17 years, our patient was a young female case of coeliac crisis. However, like in our patient, a higher incidence of coeliac crisis was associated with the human leucocyte antigen (HLA)-DQ2 haplotype, versus HLA-DQ8, and a severe (Marsh-Oberhüber 3c) duodenal mucosa atrophy. Notably, there is no clear correlation between the antitissue transglutaminase 2 IgA antibody titre and coeliac crisis onset/severity, as confirmed by our case report.Conclusions The present case highlights that CD may manifest quite abruptly with a severe malabsorption syndrome, that is, electrolyte abnormalities and hypoproteinaemia. Our case should alert physicians, in particular those in the emergency setting, that even a typically chronic disorder, such as CD, may show life-threatening complications requiring urgent management.